Determinants of perceived information need for emerging ICT adoption: A study of UK small service businesses. Issue 2 (30th May 2019) - Eze, Sunday C.; Olatunji, Sulaimon; Chinedu-Eze, Vera Chinwendu; Bello, Adenike O.; Ayeni, Adebanji; Peter, Fred
Abstract : Purpose: Most studies in information behaviour have focussed on information behaviour aspects such as environmental uncertainty, scanning behaviour of top management executives, student and women information behaviour, information source and credibility, while little is known about the information behaviour of small- and medium-sized enterprises (SMEs) when the need for emerging information and communication technology (EICT) adoption decision-making arises. This paper, therefore, aims to explore the major determinants of perceived information need for EICT adoption by UK small service-oriented businesses. Design/methodology/approach: The study adopted qualitative method to explore 13 key determinants of SME managers' information behaviour for EICT adoption decision-making by using both unstructured and semi-structured interviews at two different stages with 20 participants drawn purposeful from Luton directories. Findings: The study developed an extended technology, organisation and environment (TOE) framework by identifying and incorporating the information context which helped to unveil 13 key determinants of perceived information need and their impact on EICT adoption decision-making in SMEs. This further provided insight into understanding SMEs' information behaviour. While the determinants associated with TOE and information contexts influence SMEs' perceived information need for EICT adoption, the extent at which these four constructs shape SMEs' perceived information need for EICT adoption decision-making differs. Research limitations/implications: The limitation of this study emerged because of the use of qualitative methodologies in relation to the research design, rigour in the collection and management of the large volume of the raw data, the data analysis and the credibility of the findings. This may lead to unforeseen respondent – and research – bias in the data analysis, which may lead to limited understanding of alternatives and insights into the key determinants of perceived information need for EICT adoption decision. Hence, other measures and approaches such as case study and mix-method could be deployed to further validate the findings. Also, one of the limitations of qualitative study has been the issue of theoretical generalizability of the framework. The generalizability of the formwork needs to be established across a wider range of population. Future studies may apply a confirmatory statistical techniques to test and ascertain the validity and reliability of the framework across a wider population. Such studies may be used as a benchmark for the theoretical constructs and the factors that may lead to success or failure of mobile marketing technology adoption. Originality/value: The study has further enriched TOE framework and provided an analytical dimension for exploring key determinants of SMEs' perceived information need for EICT adoption decision-making. It also demonstrates the capacity to provide a reliable explanation of the determinants and serves as a tool for evaluating the benefits or challenges of SMEs' information behaviours when the need for EICT adoption arises.